Optimal programming of cardiac resynchronisation therapy with His bundle pacing based on aortic velocity time integral in patients with congestive heart failure and permanent atrial fibrillation. (25th November 2020) - Boczar, K; Zabek, A; Slawuta, A; Debski, M; Gajek, J; Lelakowski, J; Malecka, B
Abstract: Background: Cardiac resynchronisation therapy (CRT) in patients with permanent atrial fibrillation (AF) is usually less effective than in sinus rhythm patients. Recent evidence has shown that His bundle pacing (HBP) might be a valuable alternative to conventional pacing systems resulting in more physiologic electrical activation of the heart. Currently, there is a need to identify the optimal way of CRT + HBP programming in patients with congestive heart failure (CHF) and permanent AF to achieve high cardiac output and improve physical capacity and survival. Purpose: The aim of this study was to evaluate the impact of CRT + HBP programming on cardiac output in the early post-operative measurements. Methods: We included consecutive patients with: 1. permanent AF, 2. CHF in NYHA class III-IV, 3. bundle branch block with QRS >130 ms or QRS <130 ms and high expected requirement of ventricular pacing, 4. severely reduced left ventricular ejection fraction (LVEF) ≤35%, 5. CHF refractory to optimal medical therapy, 6. implanted CRT + HBP. All patients gave informed consent for CRT + HBP implantation and optimization of device programming. During the early post-operative phase, we aimed to optimize CRT + HBP settings in order to achieve the highest cardiac output assessed by repeated echocardiographic measurements of aortic velocity time integral at various pacing programs (Table 1). Then, we selected the optimal pacing settings of CRT + HBP for each individual patient. Results: Study included 17 consecutive patients aged 71.5±6.3 years, 12 were male. Mean LVEF was 24% and median NYHA class was III. The most efficacious method of pacing in terms of aortic VTI was HBP combined with left ventricular pacing (LV) which resulted in median VTI of 22.5. HBP + LV was superior to right ventricular pacing (RV): VTI of 22.5 vs 18.5, P=0.003 and outperformed biventricular pacing: VTI 22.5 vs 18.7, P=0.019. Detailed results are shown in Figure 1. Conclusion: His bundle pacing coupled with LV pacing proved to be the most advantageous pacing program setting with regard to cardiac output and it performed significantly better than RV pacing only or biventricular pacing. Our observation supports the use of His bundle pacing in CRT systems in patients with CHF and permanent AF. Funding Acknowledgement: Type of funding source: None